Formation of a common thesaurus project - Кармазина, Лилия Леонидовна; Руликова, Наталия Сергеевна (Eastern-European Journal of Enterprise Technologies, 2010)
The process of forming a common thesaurus of the project is described in the article with the help of a control message thesaurus that allows you to create a common information space of the project.